Design and application of a new control system for tokamak ECRH power supply. Issue 3 (3rd March 2016) - Hao, Xu; Zhang, Jian; Huang, Yiyun
ABSTRACT: The biggest challenge of designing and building tokamak electron cyclotron resonance heating (ECRH) pulse step modulation (PSM) power supply is satisfying its required output voltage rising time to be less than 100 µs while suppressing the voltage overshoot to be no more than 1%. To fulfill the two requirements, a new control strategy with startup time in microsecond range is proposed in this paper, and a new control system to realize the control strategy is introduced. The control system was built and tested on 60 kV/50 A ECRH power supply. The experimental results indicate that the control system can restrain the overshoot effectively, increase response speed, and obviously improve the dynamic characteristics of the PSM power supply system. Thus, the proposed control system helps the PSM power supply to meet the design specifications.